Priority Setting of Diseases Surveillance in the Southern Thailand - ภูมิบ่อพลับ บุญชัย; จงสู่วิวัฒน์วงศ์ วีระศักดิ์; ธรรมปาโล สุวิช (Disease Control Journal, 2008)
The Epidemiology Unit, Prince of Songkla University and the Office of Disease Prevention and Control 12 Songkhla initiated the project for developing the diseases surveillance in the South-most of Thailand. Due to resource limitation, the priority setting of diseases for surveillance in the South was carried out in 2006. The questionnaires were sent to the doctors in medical school, hospitals and the Provincial Health Offices, and then the preliminary results were analyzed and commented by the experts. The result revealed that the top ten diseases of the South were HIV/AIDS, Traffic accident, Diabetes, Stroke, Ischemic Heart Disease, COPD, Liver cancer, Tuberculosis, Depression and Alcohol dependent. In the South-most, almost similar to the South, Diabetes was the first order and HIV/AIDS turned to be the 3rd order while Malaria and Dengue hemorrhagic fever were in the 7th and 8th order which followed by Tuberculosis and Depression. The surveillance systems of the top ten diseases in the South-most had quality of the data was in unsatisfied level while the basic knowledge, technology and timeliness of response for disease prevention and control were in moderate to good level. The top ten diseases from this study would be considered by the high administrators to set policy and plan to improve the disease surveillance system in the further.